Morfometría de los peces Mugil cephalus y M. curema (Mugiliformes: Mugilidae) en Veracruz, México - Pérez García, Miguel A (Universidad de Costa Rica, 1992)
Two fish species of high capture rate were studied in the NW portion of the Gulf of Mexico: Mugil cephalus and M. curema. In M. curema, standard lenght, maximum width, minimum width, predorsal lenght-I , predorsal lenght-2, and preannal lenght pre$ent a correlation higher than 0.5 in both sexes; M. cephalus presents a high correlation with standard lenght, maximum width, predorsal lenght-2, preannal lenght, and cephalic lenght. The relative growth for M. curema was negatively allometric for standard lenght and minimum width; for the other parameters growth was isometric. In M. cephalus the relative growth was allometric-negative. fol. cephalic 1enght, _ maximum width and preannal lenght, while the other measurements showed isometric growth.